Perkembangan Naratif Anak Usia Dini: Analisis Cerita Spontan berdasarkan Model Applebee - Agustina, Hani; Marzuki, Ismail; Rifa'i, Ahmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyze narrative development in early childhood using Applebee’s narrative development model. The main focus of this research is on a 3-year-and-9-month-old child’s ability to construct narrative structures through spontaneous storytelling that emerges during play. Data were collected through naturalistic observation and audio recording during free play, daily conversations, and storytelling activities. The resulting narratives were transcribed and analyzed using Applebee’s developmental stages: heap, sequence, primitive narrative, and true narrative. The findings indicate that the child’s narrative development varies, ranging from heap and sequence to primitive narrative, with some stories approaching a true narrative structure. This analysis also highlights the importance of symbolic play media and social interaction in supporting children’s narrative development. This research is expected to contribute to the development of language and literacy learning for young children through storytelling approaches